Comparative Resistance of AH26 and a New Sealer Prototype to a Bacterial Challenge - Derek Duggan; Sheng Zhong; Eric Rivera; Roland Arnold; Eric Simmons (Hindawi Limited, 2012)
Objective. This study compared the leakage resistance of a New Sealer Prototype (NSP) with a traditional sealer (AH 26) in Resilon-filled roots subjected to a bacterial challenge. Study Design. 41 roots were instrumented to ISO size 50 apically. Group 1 (𝑛=20) contained Resilon and AH 26 sealer and roots in group 2 (𝑛=21) contained Resilon and NSP. Roots were embedded in a dual-chamber model with the upper chamber containing Streptococcus mutans inoculum. Evidence of bacterial penetration was observed for 1 month. Fisher's Test was used to analyze the data. Results. 8 of 20 roots (40%) in the AH 26 group demonstrated leakage whereas 3 of 21 roots (14%) in the NSP group leaked. The difference in leakage rates was not statistically significant (𝑃=0.053). Conclusion. The traditional sealer (AH 26) demonstrated increased leakage rates compared to the New Sealer Prototype (NSP), but the difference did not reach statistical significance in this study.